2016
DOI: 10.2174/1874836801610010027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Dynamic Response of Reinforced Concrete Frame for Resisting Progressive Collapse

Abstract: Abstract:In order to investigate the dynamic response of reinforced concrete spatial frames caused by initial damages, a six-story frame model is analyzed by employing the nonlinear dynamic methodology in accordance with the alternate path method issued by General Services Administration. In this paper, the fiber model and force-based beam-column element are utilized in OpenSees. Four various scenarios are separately analyzed with incremental dynamic analysis. It is shown that the model does not collapse and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…В [8; 9] отмечено, что квазистатический анализ не обеспечивает достаточную точность, а иногда даже не гарантирует консервативного решения. Поэтому нелинейный динамический анализ остается очень важной задачей, которая изучается многими исследователями [10][11][12][13][14].…”
Section: For Citationunclassified
“…В [8; 9] отмечено, что квазистатический анализ не обеспечивает достаточную точность, а иногда даже не гарантирует консервативного решения. Поэтому нелинейный динамический анализ остается очень важной задачей, которая изучается многими исследователями [10][11][12][13][14].…”
Section: For Citationunclassified
“…The results indicated that the structure did not collapse in the scenario of corner or inner column removal, but experienced transition from moment resisting mechanism to catenary mechanism in the scenario of two side columns removal. Wang et al [12] investigated the dynamic response of a six-story frame caused by employing the nonlinear dynamic methodology. The results indicated that the internal force redistribution mainly appeared in the components adjacent to the failure column and the model had the worst capacity to resist progressive collapse in the inner column demolition scenario.…”
Section: Introductionmentioning
confidence: 99%